2014
DOI: 10.11152/mu.201.3.2066.162.rs1is2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the M and XL probes for liver fibrosis assessment by Transient Elastography

Abstract: Objective: Liver stiffness measurement (LSM) using Transient Elastography (TE) for liver fibrosis assessment is difficult to be performed in obese and overweight patients by standard M probe, thus the XL probe was developed. The aim of our paper was to assess the usefulness of the XL probe in daily clinical practice. Material and method: Our study included 216 patients (mean BMI 30.1±4.1 kg/m2) with chronic hepatopathies, in which paired measurements were made using the M (3.5MHz) and XL (2.5 MHz) probes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 25 publications
2
20
1
1
Order By: Relevance
“…We believe our results for detecting F4 differed because the LSMs obtained using the XL probe have been reported to be lower than those obtained by the M probe. 24 The rate of failure obtained using SSI on the left lobe was significantly higher than that obtained using SSI on the right lobe, and the actual values of LSMs from the left lobe were significantly higher than with the right lobe as reported previously using virtual touch tissue quantification. 25 We previously reported that 33.1% of the study cohort had a difference of at least one stage between the right and left lobes as determined by liver biopsy.…”
Section: Discussionsupporting
confidence: 56%
“…We believe our results for detecting F4 differed because the LSMs obtained using the XL probe have been reported to be lower than those obtained by the M probe. 24 The rate of failure obtained using SSI on the left lobe was significantly higher than that obtained using SSI on the right lobe, and the actual values of LSMs from the left lobe were significantly higher than with the right lobe as reported previously using virtual touch tissue quantification. 25 We previously reported that 33.1% of the study cohort had a difference of at least one stage between the right and left lobes as determined by liver biopsy.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, it is difficult in patients with a high body mass index or narrow intercostal spaces 28 , 29 . Recently, a new FibroScan probe (XL probe) has been developed to lessen the failure rate in obese patients, and its good efficacy has been shown in some investigations 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…It can be used to accurately detect early hepatic fibrosis, 24 advanced fibrosis, 25 and cirrhosis 8 , 9 . Additionally, the recently developed XL probe has improved the feasibility of FibroScan in obese patients 26 , 27 . Nevertheless, there are technical limitations that may prevent accurate liver stiffness measurement in patients with ascites, severe hepatic atrophy, and narrow intercostal spaces 28 , 29 …”
mentioning
confidence: 99%
“…The main disadvantages are that it cannot be performed in patients with ascites [7], and that it lacks B-mode gray scale ultrasound visualization of the liver. Furthermore, the method's reliability decreases from normal weight to overweight and obese patients [21]; this disadvantage has been partially overcame by the use of the XL probe [22,23]. Previous studies have shown that there are confounding factors that can increase LS values by TE: high levels of aminotransferases [24], extrahepatic cholestasis [25] and liver congestion in heart failure [26].…”
Section: Introductionmentioning
confidence: 99%